Prevalence of Spinal Muscular Atrophy in the Era of Disease-Modifying Therapies: An Italian Nationwide Survey. (14th March 2023) - Coratti, Giorgia; Ricci, Martina; Capasso, Anna; D'amico, Adele; Sansone, Valeria; Bruno, Claudio; Messina, Sonia; Ricci, Federica; Mongini, Tiziana; Coccia, Michela; Siciliano, Gabriele; Pegoraro, Elena; et al.
Abstract : Objective: Spinal muscular atrophy (SMA) is a neurodegenerative disorder caused by mutations in the SMN1 gene. The aim of this study was to assess the prevalence of SMA and treatment prescription in Italy. Methods: An online survey was distributed to 36 centers identified by the Italian government as referral centers for SMA. Data on the number of patients with SMA subdivided according to age, type, SMN2 copy number, and treatment were collected. Results: One thousand two hundred fifty-five patients with SMA are currently followed in the Italian centers with an estimated prevalence of 2.12/100, 000. Of the 1, 255, 284 were type I, 470 type II, 467 type III, and 15 type IV with estimated prevalence of 0.48, 0.79, 0.79 and 0.02/100, 000, respectively. Three patients with SMA 0 and 16 presymptomatic patients were also included. Approximately 85% were receiving one of the available treatments. The percentage of treated patients decreased with decreasing severity (SMA I: 95.77%, SMA II: 85.11%, SMA III: 79.01%). Discussion: The results provide for the first time an estimate of the prevalence of SMA at the national level and the current distribution of patients treated with the available therapeutical options. These data provide a baseline to assess future changes in relation to the evolving therapeutical scenario.